On the dynamics of process innovative activity: an empirical investigation using panel data - Heinz König; François Laisney; Michael Lechner; Winfried Pohlmeier (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
This paper addresses three major aspects of firms' process innovative activity: forward- looking behaviour, uncertainty w.r.t. returns of R&D investments, and oligopolistic competition on the product market. Assuming that R&D expenditures are cost-reducing investments, we derive an Euler equation for process innovations and discuss alternative panel econometric approaches suitable to the case where only qualitative information is available. Empirical results are based on an unbalanced panel of German manufacturing firms for 1984-1989 and suggest that the Schumpeterian causality from firm size to innovation activity might in fact be attributed, at least partly, to heterogeneity in the perception of process innovative success.
Keywords: 330; Innovation; Marktstruktur; Betriebsgröße; Mikroökonometrie; Deutschland